The implementation of digital application in reducing Dengue Hemorrhagic Fever (DHF) infection rate from an economic loss perspective as an effort to achieve the Sustainable Development Goals - Wahyu Gito Putro; Tri Okta Ratnaningtyas; Fenita Purnama Sari Indah; Adhy Purnawan; Zaki Maulana Riski (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus transmitted through the Aedes aegypti mosquito and is most commonly found in tropical regions. In contemporary society, there is significant emphasis on infectious diseases. DHF is a tropical disease that falls under the third indicator of the Sustainable Development Goals (SDGs). DHF poses a significant global public health problem. Currently, its prevalence is spread across more than 100 countries worldwide. Over three decades, the severity of DHF has shown a significant increase across the Southeast Asian region. In 2021, Indonesia recorded a total of 73,518 DHF cases with 705 fatalities. In 2022, there were 143,266 reported cases resulting in 1,237 deaths. As of March 2023, there have been a total of 17,434 reported cases with 141 fatalities. These DHF case incidence figures indicate a considerable increase.Purpose: To reduce DHF cases in South Tangerang City by creating an innovative digital application which is called “Pakar” from an economic loss perspective.Method: This research adopts a mixed-method approach with exploratory research. The research begins with a qualitative phase to design the application, followed by a quantitative phase to assess the effectiveness of the developed application. The study commences with a Focus Group Discussion (FGD) involving various stakeholders, including the South Tangerang City Health Office, public health centers, and community health workers. Subsequently, the application is developed and tested in selected pilot areas as an initial project. Further testing is conducted using a one-group pre-test post-test design. The experimental procedure includes a pre-test as an initial observation, followed by the intervention, and concludes with a post-test as a final observation.Results: During the pre-test, it was observed that DHF patients had a moderate level of knowledge, with a cumulative percentage of 46%. In contrast, the majority of respondents in the post-test had a high level of knowledge regarding DHF diagnosis, with a percentage of 76%. The paired t-test showed a t-value of -6.306 and the corresponding probability or significance value of 0.000 (p < 0.005).Conclusion: The expert system application, as an innovative approach for DHF mitigation and the experimental assessment of economic impact, is effective as indicated by the pre-post test. Furthermore, it is crucial to consider the economic impact of the costs incurred by DHF patients by placing greater emphasis on improving environmental cleanliness efforts.